PENGARUH BIAYA PRODUKSI DAN KUALITAS TERHADAP PENDAPATAN USAHA GARAM DI KABUPATEN SUMENEP - Alwina Fariqoh Amaliyah; Nugroho , Prasetyo (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2024)
As an archipelagic country, salt is one of the main commodities in Indonesia. In Kalianget Village, Sumenep Regency, salt farmers are starting to transform using modern production methods which use geomembrane media as a salt production table. These changes will certainly affect the total production costs and quality of the salt produced. This research aims to determine whether there is an influence of production costs and the quality of salt products on salt business income in Sumenep Regency, especially in Karanganyar Village, Kalianget District. The research used a quantitative approach with 30 salt farmers as respondents. The instrument tests carried out were multiple linear regression tests, partial tests and simultaneous tests by testing production costs (X1), salt quality (X2) and farmer income (Y). The research results show that salt business income in Sumenep Regency is significantly influenced, both simultaneously and partially, by the total production costs and quality of the salt produced.